Design and Synthesis of Tetrandrine Derivatives as Potential Anti‐tumor Agents Against A549 Cell Lines. Issue 1 (3rd January 2019) - Niu, Nana; Jin, Tao; Li, Xia; Xu, Jinfang; Qu, Tingli; Bodwell, Graham J.; Zhao, Zhengbao
Abstract: Tetrandrine (1 ) was converted to 5‐bromotetrandrine (2 ) using a mild oxidative system (DMSO/HBr). Suzuki‐Miyaura and Sonogashira cross‐coupling reactions were then employed to yield a set of 5‐substituted tetrandrine derivatives. A total of 19 new compounds was synthesized and they were characterized by 1 H NMR, 13 C NMR and HRMS. Their antiproliferative activities against A549 cell lines in vitro were evaluated using the MTT assay. Most of the compounds were found to possess significant inhibitory activities and compound7 had the highest (IC50 = 3.04 μM). Further studies on the mechanism demonstrated by compound7 showed that it promotes apoptosis of A549 cells in a dose‐dependent manner and reduces the mitochondrial membrane potential. Western blot results showed that the compound up‐regulated the levels of Bax protein and down‐regulated the level of Bcl‐2 protein. Compared to the control group, the expression of cleaved‐caspase 3 and cleaved‐PARP in cells was significantly increased. Abstract : A mild brominating reagent (HBr/DMSO) has been employed to brominate tetrandrine very selectively at the 5 position. The resulting bromide was used to synthesize a series of aryl and alkynyl tetrandrine derivatives, the most active of which was found to have IC50 = 3.04 μM against A549 cell lines. It was found that this compound exerted its effect by inducing apoptosis of A549 cells through the mitochondrial pathway.